Pilot PET Study to Assess the Functional Interplay Between ABCB1 and ABCG2 at the Human Blood–Brain Barrier. Issue 2 (9th May 2016) - Bauer, M; Römermann, K; Karch, R; Wulkersdorfer, B; Stanek, J; Philippe, C; Maier‐Salamon, A; Haslacher, H; Jungbauer, C; Wadsak, W; Jäger, W; Löscher, W; et al.
Abstract : ABCB1 and ABCG2 work together at the blood–brain barrier (BBB) to limit brain distribution of dual ABCB1/ABCG2 substrates. In this pilot study we used positron emission tomography (PET) to assess brain distribution of two model ABCB1/ABCG2 substrates ([ 11 C]elacridar and [ 11 C]tariquidar) in healthy subjects without (c.421CC) or with (c.421CA) the ABCG2 single‐nucleotide polymorphism (SNP) c.421C>A. Subjects underwent PET scans under conditions when ABCB1 and ABCG2 were functional and during ABCB1 inhibition with high‐dose tariquidar. In contrast to the ABCB1‐selective substrate ( R )‐[ 11 C]verapamil, [ 11 C]elacridar and [ 11 C]tariquidar showed only moderate increases in brain distribution during ABCB1 inhibition. This provides evidence for a functional interplay between ABCB1 and ABCG2 at the human BBB and suggests that both ABCB1 and ABCG2 need to be inhibited to achieve substantial increases in brain distribution of dual ABCB1/ABCG2 substrates. During ABCB1 inhibition c.421CA subjects had significantly higher increases in [ 11 C]tariquidar brain distribution than c.421CC subjects, pointing to impaired cerebral ABCG2 function.